The Public Relations of the Bengkulu's People Representative Council Candidates - Heri Budianto; Novi Erlita (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2020)
Along with political development, public relations professions have become a more widespread profession used by many organizations. In politics, public relations is useful for building a positive image in people's minds for particular purposes. In light of that, the research attempted to analyze and describe political public relations in building the reputation of the 2019 legislative candidates for Indonesia's People Representative of the Republic of Indonesia in Bengkulu Province. The research was designed with a case-study method, and the research found that the candidates investigated had no conceptual knowledge regarding political public relations strategy. Consequently, their public relations activities, in terms of political communication, did not work effectively. The research also found that the candidates investigated, which was running in Bengkulu province, had not managed their images and relations with media in terms of political public relations. Finally, the research found that political public relations were still conducted traditionally, making the impact less strong to furnish the image of the candidates.